Relationship between the bioavailability and molecular properties of angiotensin II receptor antagonists - Trbojević, Jovana B.; Odović, Jadranka V.; Trbojević-Stanković, Jasna B.; Nešić, Dejan M.; Jelić, Ratomir M. (Archives of Biological Sciences, 2016)
In the present study, we investigated the relationships between several molecular properties and bioavailability data for seven of the most commonly prescribed angiotensin II receptor antagonists (also known as angiotensin II receptor blockers (ARBs) or sartans), candesartan, eprosartan, irbesartan, losartan, olmesartan, telmisartan and valsartan. The molecular descriptors of ARBs are:, aqueous solubility (logS values), polar surface area (PSA), molecular weight (Mw), volume value (Vol), lipophilicity (logP values) and the acidity descriptor (pKa1). The respective descriptors were calculated using four different software packages. The relevant bioavailability data were obtained from literature. Among calculated molecular descriptors, simple linear regression analysis showed the best correlation between bioavailability data and the lipophilicity descriptor, logP (R2=0.568). Multiple linear regression established good correlations between bioavailability and the lipophilicity descriptor, logP, using the molecular weight, Mw, or the acidity descriptor, pKa1, as an additional, independent variable (with R2=0.661 and 0.682, respectively). Finally, excluding candesartan from the calculations resulted in a very good correlation (R2=0.852) between the remaining ARB bioavailability